Gambaran Kadar SGPT pada Pasien Tuberculosis Multidrug Resistant (TB-MDR) - Meisika Damayanti; Surati Surati (Jaringan Laboratorium Medis, 2020)
Multidrug Resistant Tuberculosis (MDR-TB) has recently become a health threat in Indonesia. The clinical management of MDR TB is more complicated than that of ordinary TB. Hepatotoxicity or commonly known as Anti-Tuberculosis Drug-induced Hepatotoxicity (ATDH) is a serious effect of OAT that often occurs. The basic parameter for diagnosing or following up the presence of impaired liver function is the SGPT examination. The purpose of this study was to describe the level of SGPT in MDR-TB patients at the Kendal District Health Center. This study is an observational (non-experimental) study with descriptive research criteria with a cross sectional approach which was conducted on 7 MDR-TB patients at Kendal I Health Center, Kaliwungu Health Center, and South Kaliwungu Health Center with total sampling technique. The results of the study: obtained SGPT levels in 7 patients with MDR-TB there were 7 research respondents (100%) had normal SGPT levels with the lowest level of 2.17 U/L and the highest level of 37.75 U/L and the average level of SGPT ie 18.01 U/L. TB mostly attacks the age group of 56-65 years (57%). Males (57%) were the patients with the most TB cases. The most OAT consumption time was in the continuation phase (100%). Diabetes is a disease that often accompanies TB patients. The conclusion of this study is that from 7 research subjects, MDR-TB patients had SGPT levels that were in the normal range.